Using games in the teaching of grammar to English language learners - M. Ali, Aziza; Gupta, Sonia Dutta; Aralas, Dalia; Ismail, Lilliati; Othman, Moomala (Faculty of Educational Studies, Universiti Putra Malaysia, 2018)
The use of games in teaching is often claimed to spark interest and promote student engagement in the learning process. This paper reviews the theory involved and classifies the various types of games used in teaching grammar in the English language classroom. Ten research studies involving young to adult learners are analysed for this purpose. Apart from motivating and engaging learners, the paper also highlights other advantages of using games in teaching grammar. No doubt, the use of games is much more interesting than the traditional method. However it is important for teacher to match games to the teaching grammar syllabus.